Wales says yes : devolution and the 2011 Welsh referendum - Wyn Jones, Richard (University of Wales Press, 2012)
Wales Says Yesprovides the definitive account and analysis of the March 2011 Welsh referendum. Drawing on extensive historical research, the book explains the background to the referendum, why it was held, and what was at stake. The book also explains how the rival Yes and No campaigns emerged, and the varying degree of success with which they functioned. Finally, it considers what the results may mean for the future of both Wales and the United Kingdom.